Understanding older adults’ adoption of smart product-service systems for medication management in China: an extended UTAUT model approach - Fu, Ruochen; Ma, Xiaofei (Frontiers in Public Health, 2025)
The rapid aging of China’s population is intensifying the burden of chronic disease management and driving a shift toward home-based care supported by Smart Product-Service Systems (SPSS), such as smart pillboxes and medication management applications. However, the success of these technologies largely depends on their acceptance and use by older adults. This study aims to explore the behavioral factors influencing the adoption of SPSS for medication management among older adult users in China, using an extended Unified Theory of Acceptance and Use of Technology model. To better capture the complex interactions between the service delivery environment and users’ personal capabilities and psychological states, the model incorporates three additional constructs: Self-Efficacy, Health Consciousness, and Medical Service Satisfaction. Structural Equation Modeling based on Partial Least Squares was employed to validate the model using empirical data collected from older adult respondents in China. The results show that Performance Expectancy, Effort Expectancy, Social Influence, Self-Efficacy, Health Consciousness, and Medical Service Satisfaction all significantly influence behavioral intention, whereas Facilitating Conditions did not demonstrate a significant effect. These findings highlight that, within the Chinese cultural context, family support and intrinsic health motivation are more critical than external infrastructure in shaping technology adoption. This study contributes to a deeper theoretical understanding of health technology adoption among older adults and offers practical insights for SPSS developers. It underscores the importance of culturally adapted and user-friendly smart systems to improve medication adherence and health outcomes in aging societies.